Growing cycle of Hedysarum coronarium L. (sulla): relationship between plant density, stem length, forage yield and phytomass partitioning - Sulas L.; Stangoni A.P.; Re G.A.; Ledda L. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Sulla (Hedysarum coronarium L.) is a biennal Mediterranean legume and its forage production is typically concentrated in the year after sowing. The main objective of this research was to evaluate the plant dynamic, height, forage production and phytomass partitioning under undisturbate herbage accumulation of the sulla grown at agronomic plant density. When compared to the second year, the first year crop of sulla was characterised by a shorter growing season, lower dry matter per plant, stem length, stem contribution to the total dry matter yield. Plant density and contributions of leaflets, petioles and racemes were higher. Results have evidenced substantial and contrasting differences in sulla meadow structure and productivity, during each year of the biennium cycle, to be taken into account for an appropriate management of the sulla meadow.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)